A pluralização limitada de trajetórias familiares em Portugal - Ramos, Vasco (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2016)
Using a life course perspective, this paper tackles the pluralisation of family trajectories in Portugal. We draw on data from a cross-cohort survey, which included a retrospective lifecalendar, and on an innovative methodology, based on sequence and cluster analysis. Findings point to a limited pluralisation of family trajectories. A retrospective look at the trajectories of individuals dismantled idealizations of a monochromatic past but also challenged the contemporary narrative of family decline, as pluralisation and individualization trends do not discard some of the main tenets of family life cycle.